A rare case of alcoholic pellagra encephalopathy with startle myoclonus and marked response to niacin therapy: time for a new dictum?. (22nd April 2013) - Sharma, Bhawna; Sannegowda, Raghavendra Bakki; Jain, Rahul; Dubey, Parul; Prakash, Swayam
Abstract : We report a case of 56-year-old man, chronic alcoholic, presented to us with progressive weakness in all the four limbs with stiffness and gait disturbance since 1-year associated with cognitive impairment. On examination he had mild confusion, spastic quadriparesis with brisk reflexes, extensor plantars and cerebellar features. During the hospital stay myoclonus was noticed in the patient, which was startle in nature. He did not have dermatitis, ascites or any stigmata of liver failure. MRI of brain revealed bilateral subdural effusion, left focal subarachnoid haemorrhage at perisylvian area and diffuse cortical atrophy. He was treated with supportive measures including thiamine with which his condition worsened. His serum niacin was low. With a possibility of alcoholic pellagra encephalopathy (APE) the patient was treated with niacin. His clinical condition improved drastically over next 1 week and startle myoclonus disappeared, favouring the diagnosis of APE though multiple confounding factors were present.